Chopped fiber prestress reinforced active core and preparation method thereof
By adding chopped fibers unloaded after stretching to the creep stage to the fluoropolymer-based active material system, a prestressed active material core was prepared, which solved the problem of insufficient compressive and tensile strength of the traditional active core, and significantly improved the damage ability of the invasion warhead.
Patent Information
- Application Number
- CN202411893196.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The traditional high-energy fluoropolymer-based active core has low compressive strength and tensile strength in the invading warhead, which is easy to break and scatter, resulting in difficult damage power in multi-layer target scenarios.
A viscoelastic chopped fiber unloaded after stretching to the creep stage is added to the fluoropolymer-based active material system to prepare a prestressed active material core. The prestress recovery effect of chopped fibers significantly improves the compressive and tensile strength of the active core.
The compressive strength and tensile strength of the active core are improved, the fragmentation and scattering phenomenon is reduced, the damage ability to multi-layer targets is enhanced, and the damage power of the invasion warhead is significantly improved.
Smart Images

Figure CN119687733A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of explosive warheads, and in particular to a chopped fiber prestressed reinforced active core and a preparation method thereof. Background Art
[0002] The explosive warhead is the main type of warhead for attacking multi-layered large ships and buildings. It is mainly composed of a high-strength metal shell, high-energy explosive charge, fuze, etc. The basic working principle is that the warhead relies on kinetic energy to penetrate the target, and through the fuze layer counting / timing function, after the warhead penetrates a certain number of target structures or penetrates to a certain depth of the target, the high-energy explosive charge is detonated to damage the target.
[0003] With the improvement of target protection performance, in order to achieve efficient destruction of multi-layered large ships and building targets, the terminal velocity of the explosive warhead must be continuously improved. In the process of acting on the target, the impact load and overload borne by the explosive warhead structure are continuously increased, which poses severe challenges to the reliable timing / layer / depth detonation of the fuze and the stability of the explosive charge, and significantly restricts the application of traditional explosive warheads and the technical development of explosive warheads with the basic technology system of fuze-explosive.
[0004] Active materials are a new type of high-energy-density energetic material with typical characteristics of "quasi-inert insensitivity, quasi-explosive energetics, micro-millisecond activation delay, and non-self-sustaining explosive energy release". Under normal conditions, they are in an inert metastable state with good mechanical properties. However, under strong impact loads, they will be activated and undergo chemical reactions, rapidly and violently releasing a large amount of chemical energy, producing shock waves, heat, combustion and other effects. Taking advantage of the technical characteristics and advantages of active materials, the active material core replaces the explosive to form an active invasive and explosive warhead, which does not require a fuze or explosive, can adapt to the extreme speed and load characteristics of the projectile, and give full play to the advantages of invasive and explosive combined damage.
[0005] From the perspective of the mechanism of action of the active explosive warhead, during the high-speed penetration of the target, the strong impact load is transmitted to the warhead structure, which activates the active core material on the one hand and causes the warhead shell to fail and be damaged on the other hand. After the failed shell breaks and loses its restraint, the axial and radial stresses of the activated active core are released, causing it to break and fly, triggering the active core material to deflagrate, causing combined explosive damage to the target.
[0006] However, the currently widely used high-energy fluoropolymer-based active core materials are mainly composed of fluoropolymer matrix, inert metal powder, active metal powder, modified additives and other components. Since they can only be prepared by mixing / pressing process and cannot be sintered at high temperature, there are significant problems such as low compressive strength (~130MPa) and tensile strength (~20MPa). Under the aforementioned axial and radial stress release, the active core is prone to breakage and scattering. In the scenario of acting on multi-layer targets, it is easy to result in too few remaining active cores acting on subsequent target structures, which significantly limits the destructive power of the active explosive warhead.
[0007] At present, the main means to improve the adaptability of high-energy fluoropolymer-based active cores in explosive warheads is to add a certain thickness of metal or non-metal coating structure to the outside of the core, but this will directly lead to a reduction in the effective mass of the high-energy active core, affecting the improvement of the power of the explosive warhead.
[0008] Therefore, combining the typical target characteristics of active explosive warheads and the requirements for active cores, inventing new active core preparation processes and improving the strength of active cores are of great significance to the development and application of active explosive warhead technology. Summary of the invention
[0009] In view of this, the present invention provides a chopped fiber prestressed reinforced active core, in which viscoelastic chopped fibers that are stretched to the creep stage and then unloaded are added to a fluoropolymer-based active material system. The prepared active material core will have significantly improved strength under the continuous recovery stress of the chopped fibers, thereby solving the bottleneck problems of the active core being too easy to break and scatter after the stress of the target shell of the active explosive warhead is released, too little active core remaining when acting on subsequent targets, and difficulty in exerting the combined destructive power of the explosive warhead.
[0010] The chopped fiber prestressed reinforced active core of the present invention comprises an active core body and a prestressed chopped fiber material, wherein the mass of the prestressed chopped fiber material is 5% to 15% of the total mass, and the active core body accounts for 85% to 95% of the total mass;
[0011] The prestressed short-cut fiber material is formed by stretching the fiber material into the creep stage and then cutting it into short pieces. The length of the prestressed short-cut fiber material is 50 to 100 times the particle size of the active metal powder in the active core body.
[0012] Preferably, the fiber material is nylon or has a density of 0.94-0.98 g / cm 3 , UHMW-PE with tensile strength>20MPa and elongation at break>250%.
[0013] Preferably, the fiber material is stretched by applying a constant tensile stress, the amplitude of the applied constant tensile stress is 30% to 40% of the breaking limit of the fiber material, the tensile stress action time is 6 to 24 hours, so that the fiber material enters a creep stage, and a shrinkage prestress is generated after the tensile stress is unloaded, and the stretched fiber material is chopped to obtain a prestressed chopped fiber material.
[0014] Preferably, a coupling agent is used to treat the surface of the prestressed chopped fibers.
[0015] Preferably, the coupling agent is a silane coupling agent, a titanate coupling agent or an aluminate coupling agent.
[0016] Preferably, the amount of coupling agent m is determined based on the mass of the chopped fibers:
[0017] m=m1*s1 / S
[0018] Where m1 is the mass of the chopped fibers, s1 is the specific surface area of the chopped fibers, and S is the minimum wetting area of the coupling agent.
[0019] Preferably, the active core body adopts polymer matrix / inert metal powder / active metal powder, including 20-80% matrix powder, 0-50% inert metal powder and 20-50% active metal powder by mass, or adopts an active core body containing TiH2, MgH2, ZrH2, MoO3, Fe2O3 or MnO2 modified additives.
[0020] The present invention also provides a method for preparing the above-mentioned chopped fiber prestressed reinforced active core, comprising:
[0021] S1, drying and sieving the component powders according to the active core body formula;
[0022] S2, heat treating the fiber material at 100-150° C. for 0.5-2 h to eliminate residual stress in the fiber material;
[0023] S3, stretching the fiber material to make it enter a creep stage;
[0024] S4, cutting the stretched fiber material into short fibers;
[0025] S5, according to the active core formula, weigh the processed active core body component powders and chopped fiber materials according to the ratio requirements, and mix them to obtain mixed powder;
[0026] S6, adding the mixed powder into the mold, maintaining the pressure for a certain period of time under a certain molding pressure, and pressing the mixed powder into an active core sample.
[0027] Preferably, in S6, when the aspect ratio of the prepared active core is not greater than 3, a unidirectional molding method is adopted; when the aspect ratio of the prepared active core is greater than 3, a bidirectional molding method is adopted; the molding pressure is determined according to the density requirement of the active core; and the holding time is 1 to 5 minutes.
[0028] Beneficial effects:
[0029] In order to solve the problem of insufficient strength of high-energy active cores prepared by traditional mixing / pressing processes, the present invention proposes adding viscoelastic chopped fibers that are stretched to the creep stage and then unloaded into a polymer-based active material system. The prepared active material core will have significantly improved compressive strength and tensile strength under the continuous recovery stress of the chopped fibers, thereby solving the bottleneck problems of the active core being too easy to break and scatter after the stress of the shell of the target being acted upon by the active explosive warhead is released, too little active core remaining when acting on subsequent targets, and the energy released by the active core being unable to effectively destroy large ships with multi-layer structures, making it difficult to exert the combined destructive power of the explosive warhead. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the structure of the active core reinforced with chopped fiber prestressing.
[0031] Among them, 1-prestressed chopped fibers, 2-matrix powder, 3-inert metal powder, 4-active metal powder.
[0032] Figure 2 Schematic diagram of stress recovery behavior of chopped fibers.
[0033] Figure 3 Schematic diagram comparing the failure behaviors of a traditional active material core and a chopped fiber prestressed reinforced active material core under tensile load.
[0034] Figure 4 This is a tensile test specimen of the chopped fiber prestressed reinforced active material core in an embodiment of the present invention.
[0035] Figure 5 Comparison of tensile stress-strain curves between the chopped fiber prestressed reinforced active material core and the traditional active material core in the embodiment of the present invention.
[0036] Figure 6 The figures are the experimental results of penetrating the target plate using the traditional active material core and the short-cut fiber prestressed reinforced active material core of the present invention; wherein (a) is the traditional active material core; (b) is the short-cut fiber prestressed reinforced active material core of the present invention. DETAILED DESCRIPTION
[0037] The present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0038] The invention provides a chopped fiber prestressed reinforced active core, comprising an active core body and a prestressed chopped fiber material, wherein the mass of the chopped fiber material is 5% to 15% of the total mass, and the mass of the active core body is 85% to 95% of the total mass.
[0039] The chopped fiber material is formed by stretching the fiber material into the creep stage and then chopped. The fiber material is generally selected from polymer-based materials with viscoelastic mechanical properties such as nylon, UHMW-PE (ultra-high molecular weight polyethylene) (density 0.94-0.98 g / cm3, tensile strength>20 MPa, elongation at break>250%).
[0040] When the fiber material is stretched, a constant tensile stress is generally applied, the tensile stress amplitude is 30-40% of the fracture limit of the fiber material, and the tensile stress action time is 6-24 hours, so that the fiber material enters the creep stage, and shrinkage prestress is generated after the tensile stress is unloaded;
[0041] Under tensile stress, the stress-strain in the fiber material satisfies the following relationship:
[0042]
[0043] Where σ is tensile stress, ε(t) is strain, and E v is the elastic constant of fiber material, η v is the viscosity constant of the fiber material, and t is the stretching time.
[0044] After the tensile stress is unloaded, the relationship between the strain in the fiber and time is:
[0045]
[0046] Where ε0 is the strain generated in the fiber material at the moment of tensile stress unloading.
[0047] The length of the chopped fibers is generally selected according to the active core body to better play its role in restoring stress, and is generally 50 to 100 times the particle size of the active metal powder in the active core body;
[0048] Preferably, the chopped fibers are surface treated with a coupling agent to improve the processing performance of the chopped fibers, thereby enabling the active core material to obtain better mechanical properties. The coupling agent is selected from silane coupling agents, titanate coupling agents or aluminate coupling agents, and is treated by mechanical mixing. The amount of coupling agent m is determined based on the mass of the chopped fibers.
[0049] m=m1*s1 / S
[0050] Where m1 is the mass of the chopped fibers, s1 is the specific surface area of the chopped fibers, and S is the minimum wetting area of the coupling agent.
[0051] The active core body can adopt a polymer matrix / inert metal powder / active metal powder formula, including 20-80% matrix powder, 0-50% inert metal powder and 20-50% active metal powder by mass. It can also adopt an active core formula containing modified additives such as TiH2, MgH2, ZrH2, MoO3, Fe2O3, MnO2, etc.
[0052] The matrix powder is generally made of materials such as PTFE (polytetrafluoroethylene), PVDF (polyvinylidene fluoride), THV (polymer of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride), etc.
[0053] The active metal powder is generally one or more materials such as aluminum, zirconium, aluminum-zirconium alloy, boron, titanium, hafnium, etc., which are selected according to the mechanical performance requirements of the active core material; the particle size of the active metal powder is selected according to the performance requirements such as the activation threshold and reaction rate of the active core material;
[0054] The inert metal powder is generally one or more materials such as tungsten, SiC, ceramics, etc., which are selected according to the mechanical performance requirements of the active core material; the particle size of the inert metal powder is selected according to the performance requirements such as the activation threshold and reaction rate of the active core material.
[0055] The working principle of the short-cut fiber prestressed reinforced active core of the present invention is:
[0056] The present invention adds prestressed chopped fiber material to the active core body. During the process of the active core penetrating the target, the recovery stress of the chopped fiber material is used to enhance the compressive strength and tensile strength of the active core, so that the active core is not easy to break and scatter when penetrating multi-layer targets, and the volume and mass of the remaining active core are increased, so that it can continue to act on the subsequent target plate structure, significantly enhancing the destructive power of the active explosive warhead.
[0057] The present invention also provides a method for preparing the above-mentioned chopped fiber prestressed reinforced active core, wherein the chopped fiber material accounts for 5% to 15% of the total mass, and the active core body accounts for 85% to 95% of the total mass; the active core body comprises 20% to 80% by mass of matrix powder, 20% to 50% by mass of active metal powder and 0% to 50% by mass of inert metal powder; the specific steps are as follows:
[0058] (1) Spread the matrix powder evenly in a shallow container and place it in a drying oven; preferably, the matrix powder should be spread evenly and flatly, with a thickness generally not greater than 1 cm;
[0059] (2) vacuuming the drying oven, setting the drying oven temperature and drying time, and drying the base powder; preferably, the drying temperature range is 50 to 70° C., and the drying time is generally set to 3 to 8 hours according to the moisture absorption degree of the powder;
[0060] (3) The dried matrix powder is passed through a 300-mesh sieve to obtain a matrix powder material with a particle size of less than 50 μm for later use;
[0061] (4) evenly spread the active metal powder in a shallow container and place it in a drying oven. After evacuating the drying oven or filling it with an inert atmosphere, dry the active metal powder for 5 to 8 hours at a temperature not exceeding 50° C. for later use.
[0062] (5) Spread the inert metal powder evenly in a shallow container and place it in a drying oven. After evacuating the drying oven or filling it with an inert atmosphere, dry the inert metal powder for 3 to 5 hours at a temperature not exceeding 50° C. and set it aside for later use;
[0063] (6) heat treating the fiber material at 100 to 150° C. for 0.5 to 2 h to eliminate residual stress in the fiber material;
[0064] (7) Then, a constant tensile stress is applied to the fiber material by a universal material testing machine or other similar device, the stress amplitude is 30 to 40% of the fracture limit of the fiber material, and the tensile stress action time is 6 to 24 hours, so that the long fiber enters the creep stage, and shrinkage prestress is generated after the tensile stress is unloaded;
[0065] (8) Cutting the stretched long fibers into short fibers; determining the length of the short fibers according to the formula of the active core body to better play its role in restoring stress, generally 50 to 100 times the particle size of the active metal powder;
[0066] (9) Surface treatment of chopped fibers with a coupling agent to improve the processing properties of the chopped fibers, thereby enabling the active core material to obtain better mechanical properties;
[0067] (10) The chopped fibers are stirred for 5 to 30 minutes, which is adjusted according to equipment conditions and stirring speed.
[0068] (11) According to the formula of the enhanced active core, the processed matrix powder, active metal powder, inert metal powder, and chopped fiber material are weighed according to the ratio requirements, and added into the mixing equipment in sequence, and the mixing time and mixing rate are set to mix the powders;
[0069] Preferably, the mixing equipment adopts a V-barrel mixer, and the mixing time and mixing rate are determined according to the total mass of the powder; the mixing environment should be dry and ventilated, and the humidity should not exceed 20% RH;
[0070] (12) adding the mixed powder into a cylindrical mold, using a unidirectional or bidirectional molding method, and after maintaining the pressure for a certain period of time under a certain molding pressure, pressing the mixed powder into a cylindrical active core sample;
[0071] Preferably, when the aspect ratio of the active core is not greater than 3, a one-way molding method is generally adopted, and when the aspect ratio of the active core is greater than 3, a two-way molding method is generally adopted; the molding pressure is determined according to the density requirements of the active core, generally 40 to 150 MPa; the holding time is generally 1 to 5 minutes.
[0072] The following is an explanation with a specific example:
[0073] Select polytetrafluoroethylene (PTFE) as the fluoropolymer matrix material, take an appropriate amount of polytetrafluoroethylene powder and spread it on an aluminum shallow bottom tray with a thickness of 5mm, place it in a drying oven, evacuate the drying oven, set the drying temperature to 50℃, and dry the polytetrafluoroethylene powder for 3 hours. The dried polytetrafluoroethylene powder is passed through a 300-mesh sieve to remove the agglomerated powder, and a dry fluoropolymer powder material with a particle size of less than 50 microns and good fluidity is obtained for standby use.
[0074] Air-atomized aluminum powder with a median particle size of 45 μm was selected as the active metal powder. An appropriate amount of aluminum powder was spread on an aluminum shallow-bottom tray with a thickness of 3 mm and placed in a drying oven. After the drying oven was filled with argon atmosphere, the drying temperature was set to 50°C. After drying the aluminum powder for 3 hours, it was temporarily stored under inert atmosphere for later use.
[0075] Ball-milled tungsten powder with a median particle size of 30 microns was selected as the inert metal powder. An appropriate amount of tungsten powder was spread on an aluminum shallow bottom tray with a thickness of 3 mm and placed in a drying oven. After the drying oven was filled with argon atmosphere, the drying temperature was set to 50°C. After the tungsten powder was dried for 3 hours, it was temporarily stored under the protection of an inert atmosphere for later use.
[0076] Polyamide nylon 66 with viscoelastic mechanical properties was selected as the long fiber material, and its tensile strength is about 50MPa. The nylon fiber was heat treated at 100℃ for 1h to eliminate the residual stress in the fiber. Then, a universal material testing machine was used to apply a constant tensile stress of 30MPa to the nylon fiber for 6h, so that the long fiber entered the creep stage, and the shrinkage prestress was generated after the tensile stress was unloaded. After that, the long nylon fiber was cut into short fibers with a length of about 4mm.
[0077] Epoxysilane was selected as a coupling agent, diluted with a mixed solution of ethanol and water (ratio 0.65:0.35), added to the chopped fibers by spraying, and stirred for about 30 minutes using a high-speed stirring device until the diluted solution was completely evaporated. The chopped fibers were then placed in a drying oven and vacuum dried at 50 degrees to complete the coupling of the chopped nylon fibers and the coupling agent for use.
[0078] According to the mass ratio of 53.68%, 21.23%, 17.99% and 7.1%, polytetrafluoroethylene powder, aluminum powder, tungsten powder and chopped fibers were weighed and added into the V-tube mixer in sequence, and mixed at a rate of 120r / min for 1 hour. During the mixing process, the humidity in the operating room was controlled to be no more than 20%RH by a dehumidifier.
[0079] The mixed powder was added into the cavity of a steel cylindrical mold with an inner diameter of 40 mm, and the mold was pressed in one direction under a pressure of 100 MPa and maintained for 3 minutes to complete the pressing. The actual density of the active core obtained was 99.98% of its theoretical density.
[0080] Based on the same process flow and parameters, without adding prestressed short fibers, an active material core material (PTFE 64.5wt.% / Al 25.51wt.% / W 9.99wt.%) with the same oxygen balance and density as the above materials was prepared as a comparison.
[0081] The two active core materials were machined into rod-shaped tensile test specimens, and two groups of quasi-static tensile mechanical property tests were carried out on each of them. The loading strain rate was 0.001s -1 .
[0082] The experimental results show that the tensile strengths of the active core material without adding prestressed short fibers in two tensile tests were 22.04MPa and 21.43MPa, respectively, and the corresponding failure strains were 0.29 and 0.26, respectively.
[0083] The tensile strengths of the short fiber prestressed reinforced active material core prepared by the present invention in two experiments were 38.57 MPa and 36.34 MPa, respectively, and the corresponding failure strains were 0.51 and 0.48, respectively.
[0084] The two active core materials were machined into cylindrical fragments and the fragment penetration test was carried out. The experimental results are as follows: Figure 6 Among them, the traditional active core material without adding prestressed short fibers failed to penetrate the target plate, and the bulge was significant. The diameter of the bulge area was about Φ60, and the maximum bulge height was 16mm ( Figure 6 (a)); The short-cut fiber prestressed reinforced active material core prepared by the present invention can penetrate the target plate, and the perforation area is 151.5mm 2 , the maximum ridge height is 9mm, and the perforation edge is in a relatively regular shear shape ( Figure 6(b)). It can be seen that the conventional active core material is prone to fragmentation during the penetration of the target plate due to its low compressive and tensile strength, resulting in weak penetration ability, and the aluminum plate cannot be penetrated. The short-cut fiber prestressed reinforced active core material prepared by the present invention has improved compressive and tensile strengths under the same projectile-target collision conditions, and its penetration ability is enhanced compared with the conventional active core material, and it can penetrate the aluminum plate and cause a plug-shaped expansion hole.
[0085] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A chopped fiber prestressed reinforced active core, characterized in that: It comprises an active core body and a prestressed chopped fiber material, wherein the mass of the prestressed chopped fiber material is 5% to 15% of the total mass, and the active core body accounts for 85% to 95% of the total mass; The prestressed short-cut fiber material is formed by stretching the fiber material into the creep stage and then cutting it into short pieces. The length of the prestressed short-cut fiber material is 50 to 100 times the particle size of the active metal powder in the active core body.
2. The chopped fiber prestressed reinforced active core according to claim 1, characterized in that: The fiber material is nylon or has a density of 0.94-0.98 g / cm 3 , UHMW-PE with tensile strength>20MPa and elongation at break>250%.
3. The chopped fiber prestressed reinforced active core according to claim 1 or 2, characterized in that: The fiber material is stretched by applying a constant tensile stress, the amplitude of the applied constant tensile stress is 30% to 40% of the fracture limit of the fiber material, and the tensile stress action time is 6 to 24 hours, so that the fiber material enters a creep stage, and a shrinkage prestress is generated after the tensile stress is unloaded. The stretched fiber material is chopped to obtain a prestressed chopped fiber material.
4. The chopped fiber prestressed reinforced active core according to claim 1, characterized in that: The prestressed chopped fibers are surface treated with a coupling agent.
5. The chopped fiber prestressed reinforced active core according to claim 4, characterized in that: The coupling agent is a silane coupling agent, a titanate coupling agent or an aluminate coupling agent.
6. The chopped fiber prestressed reinforced active core according to claim 1 or 4, characterized in that: The amount of coupling agent m is determined based on the mass of the chopped fibers: m=m1*s1 / S Where m1 is the mass of the chopped fibers, s1 is the specific surface area of the chopped fibers, and S is the minimum wetting area of the coupling agent.
7. The chopped fiber prestressed reinforced active core according to claim 1, characterized in that: The active core body adopts polymer matrix / inert metal powder / active metal powder, including 20-80% matrix powder, 0-50% inert metal powder and 20-50% active metal powder by weight, or adopts an active core body containing TiH2, MgH2, ZrH2, MoO3, Fe2O3 or MnO2 modified additives.
8. A method for preparing a chopped fiber prestressed reinforced active core as claimed in claims 1 to 7, characterized in that: include: S1, drying and sieving the component powders according to the active core body formula; S2, heat treating the fiber material at 100-150° C. for 0.5-2 h to eliminate residual stress in the fiber material; S3, stretching the fiber material to make it enter a creep stage; S4, cutting the stretched fiber material into short fibers; S5, according to the active core formula, weigh the processed active core body component powders and chopped fiber materials according to the ratio requirements, and mix them to obtain mixed powder; S6, adding the mixed powder into the mold, maintaining the pressure for a certain period of time under a certain molding pressure, and pressing the mixed powder into an active core sample.
9. A preparation method according to claim 8, characterized in that: In S6, when the aspect ratio of the prepared active core is not greater than 3, a unidirectional molding method is adopted; when the aspect ratio of the prepared active core is greater than 3, a bidirectional molding method is adopted; the molding pressure is determined according to the density requirement of the active core; and the holding time is 1 to 5 minutes.
Citation Information
Patent Citations
Fiber-reinforced rubber explosive and preparation method thereof
CN106748591A
Energy absorption and containment characteristic analysis method of foam and chopped fiber reinforced honeycomb sandwich containment casing under high-speed impact
CN116933438A
Modified basalt fiber / polyurethane vibration and noise reduction material with excellent comprehensive performance and preparation method thereof
CN116948132A
Cartridge support clamping petal of carbon fiber composite armor-piercing bullet and forming method and forming mold
CN117928314A
Inorganic fiber-metal powder paper as well as preparation method and application thereof
CN118345651A